Integrated Risk Assessment and Mitigation Strategy Prioritization for Cargo Handling Delays in Dry Bulk Port Terminals: A Combined FMEA-AHP Analysis - Parman; Agustin, Dwi Febrianti; Sophia, Alma Vita (Airlangga Journal of Innovation Management, 2025)
Operational delays in cargo handling activities represent a critical challenge for dry bulk port terminals, directly impacting vessel turnaround efficiency and port competitiveness. This research addresses the need for systematic risk identification and structured prioritization of mitigation strategies within dry bulk terminal operations. The study employed a mixed-method approach integrating Failure Mode and Effect Analysis (FMEA) with Analytical Hierarchy Process (AHP) at a major dry bulk terminal facility in Gresik, Indonesia. Primary data were collected through semi-structured expert interviews and structured questionnaires administered to five operational supervisors with minimum five-year tenure. Secondary data comprised operational records documenting 76 delay incidents across 2024. FMEA implementation identified eighteen discrete operational risk factors categorized into four domains: internal operational risks, human resource risks, system-based risks, and external environmental risks. Risk Priority Number (RPN) calculations established a hierarchical risk ranking, with four substantially elevated priority risks identified: poor truck circulation (RPN=216.75), grab equipment malfunction (RPN=194.88), weather impact (RPN=181.44), and fleet availability insufficiency (RPN=157.76). Subsequent Analytical Hierarchy Process assessment determined optimal mitigation strategy sequences for prioritized risks, emphasizing periodic organizational coordination mechanisms, preventive maintenance scheduling, capacity expansion, and adaptive operational procedures. Consistency Ratio validation confirmed expert judgment coherence (CR=0.02). Findings demonstrate that integrated FMEA-AHP frameworks provide actionable intelligence for resource allocation in port risk management.